THE INFLUENCE OF WORK LIFE BALANCE AND ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION AT PT. ANUGRAH GROUP CORPORATION, KOLAKA REGENCY - Windayani; Nehru Putri, Triwulandari; Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine the influence of work life balance and organizational culture on employee job satisfaction at PT. Anugrah Group Corporation, Kolaka Regency. Job satisfaction is a crucial factor that determines employee productivity, commitment, and retention. This research adopts a quantitative approach with a census method involving 72 permanent employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that work life balance and organizational culture both have a positive and significant effect on employee job satisfaction, both partially and simultaneously. This indicates that employees who can maintain a healthy balance between work and personal life and who work in a supportive organizational culture tend to experience higher job satisfaction. The findings highlight the importance for the company’s management to develop policies that promote flexible work arrangements and to continuously foster a positive, collaborative, and fair workplace culture. These efforts are expected to improve employees’ well-being, motivation, and overall job satisfaction, contributing to the company’s sustainable growth.